Comparative Analysis of Consumer Preferences for African Prints in Southwest Nigerian States - Adeloye, Adebayo Abiodun; Jeje, Omotunde Matthew; Kayode, Tope Dare; Kolade, Olusegun Olaiya (NIU Journal of Social Sciences, 2024)
This research investigates the diverse perceptions and preferences of consumers towards African prints in Southwest Nigeria across various age groups. The study examined the interplay of cultural, social, and economic factors shaping consumer choices in of African print fabric usage. Survey research design was adopted for the study using questionnaire as the data gathering tool. Samples were selected across the six states in Southwest Nigeria. A total of three hundred and eighty-four (384) African print consumers were sampled using random sampling technique. The data was subjected descriptive analysis, using frequency distribution, percentage, and mean score. The study revealed that users of African print fabrics across age groups have their unique perceptions and preferences in African print fabrics. It was therefore recommended that African print designers should adopt user-centred design process and focus on consumer preferences during the design process of African print fabrics. Keywords: African prints, Preference, Southwest, Nigeria.